Optimalisasi Penjualan dan Pengelolaan Keuangan UMKM Pedagang Melalui Pengenalan Fintech dan Pemanfaatan Facebook Market Place - Rezzi Hidayati; Zaenal Wafa (Lembaga Pengembangan Kinerja Dosen, 2024)
This service aims to assist Micro, Small and Medium Enterprises (MSME) traders in increasing sales and managing their finances through the introduction of financial technology (fintech) and the utilization of the Facebook Marketplace e-commerce platform. This service was carried out in response to the challenges faced by MSMEs in the digital era, especially in the aspects of increasing sales and efficiency of financial management. This service activity involves direct training and assistance to MSME players in Wanayasa District, Banjarnegara Regency. The stages of training activities include 1) survey 2) training and mentoring 3) results and evaluation. This training activity is an introduction to the basics of fintech, how to access and utilize fintech services for financial management, as well as marketing and sales strategies through Facebook Marketplace. The results of this activity show an increase in the ability of MSME traders to use fintech to better manage their finances, including in terms of transaction recording, cash flow management, and access to digital financial services. In addition, the merchants also succeeded in increasing the visibility and sales of their products through Facebook Marketplace.Thus, the introduction of fintech and the utilization of Facebook Marketplace are proven to support the optimization of sales and financial management of MSMEs.